2021
DOI: 10.1186/s13054-021-03734-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of distinct clinical phenotypes of acute respiratory distress syndrome with differential responses to treatment

Abstract: Background Acute respiratory distress syndrome (ARDS) is a heterogeneous syndrome, and the identification of homogeneous subgroups and phenotypes is the first step toward precision critical care. We aimed to explore whether ARDS phenotypes can be identified using clinical data, are reproducible and are associated with clinical outcomes and treatment response. Methods This study is based on a retrospective analysis of data from the telehealth intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
(28 reference statements)
1
22
0
Order By: Relevance
“…In our sepsisassociated ARDS patient classification, Cluster 0 patients were Frontiers in Physiology frontiersin.org 13 the least ill and had poor lung recruitability, which is equivalent to the hypoinflammatory phenotype classification of ARDS by Calfee et al (2014) in 2014; mortality is lower with low PEEP. In type I ARDS according to the classification of Liu et al (2021), low PEEP had a lower 60-day mortality rate than high PEEP, which may be because the use of lower PEEP in these patients is sufficient to maintain alveolar inflation and increase functional residual capacity. On the other hand, the patients of Cluster 1 and Cluster 2 have more severe illness, which is equivalent to hyperinflammatory ARDS patients, with a higher mortality rate than Cluster 0.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In our sepsisassociated ARDS patient classification, Cluster 0 patients were Frontiers in Physiology frontiersin.org 13 the least ill and had poor lung recruitability, which is equivalent to the hypoinflammatory phenotype classification of ARDS by Calfee et al (2014) in 2014; mortality is lower with low PEEP. In type I ARDS according to the classification of Liu et al (2021), low PEEP had a lower 60-day mortality rate than high PEEP, which may be because the use of lower PEEP in these patients is sufficient to maintain alveolar inflation and increase functional residual capacity. On the other hand, the patients of Cluster 1 and Cluster 2 have more severe illness, which is equivalent to hyperinflammatory ARDS patients, with a higher mortality rate than Cluster 0.…”
Section: Discussionmentioning
confidence: 91%
“…However, the determination of biological phenotype is inseparable from the definition of plasma biomarkers, and thus this is difficult to determine at bedside. In 2021, Liu et al (2021) used fast and easily available clinical indicators to classify ARDS patients into three clinical phenotypes. These subtypes were not defined by plasma biomarkers and were thus more convenient for rapid clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, two studies declared that inflammatory phenotypes could also be accurately predicted without biomarker data using supervised learning approaches [24,25]. Another study identified three phenotypes of ARDS based on routine medical data in the eICU database [26]. From another perspective, we concentrated primarily on pulmonary mechanics and organ function, including mechanical power and ventilatory ratio, which were both significantly associated with mortality in ARDS [27,28], and had never been employed to identify phenotypes in traditional ARDS.…”
Section: Discussionmentioning
confidence: 99%